Mergers, Acquisitions, and Corporate Restructurings / Fourth Edition - Gaughan Patric A (John Wiley And Sons, Inc, 2007)
An indispensable tool in building a new generation of re-engineered companies with the power and resources to compete an a Global playing field. Preface, Background, Introduction, History of Mergers, Legal Framework, Merger Strategy, Hostile Takeovers, Antitakeover Measures, Takeover Tactics, Going Private Transactions and Leveraged Buyouts, Leveraged Buyouts, Trends in the Financing of Takeovers and Going Private Transactions, Employee Stock Ownership Plans, Corporate Restructuring, Corporate Restructuring, Restructuring in Bankruptcy, Corporate Governance, Joint Ventures and Strategic Alliances, Valuation, Tax Issues, Glossary, Index.